Implementierungswissenschaft: Konzepte, Rahmenmodelle und ein illustratives Anwendungsbeispiel der PRONAM. - McCutchan, Tom; López-Sánchez, Marlene; Rivas-Ruiz, Rodolfo (Revista Medica del IMSS)
This editorial discusses the "know-do gap" within the healthcare system, where evidence-based research findings often fail to translate into routine clinical practice. It introduces implementation science as a solution, highlighting the Consolidated Framework for Implementation Research (CFIR) alongside other frameworks that explain the factors influencing various outcomes in the implementation of evidence-based clinical practice. The methodology employs a brief conceptual application of these frameworks to the National Medical Care Protocols (PRONAM) in Mexico. We believe that the use of these tools will contribute to the successful integration of PRONAM by addressing contextual barriers, facilitators and sustainability. Implementation science empowers decision-makers to deliver effective, high-quality care to patients.